The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1371/journal.pone.0087623
|View full text |Cite
|
Sign up to set email alerts
|

Oriental Medicine Kyung-Ok-Ko Prevents and Alleviates Dehydroepiandrosterone-Induced Polycystic Ovarian Syndrome in Rats

Abstract: Kyung-Ok-Ko (KOK), a traditional herbal prescription composed of Rehmannia glutinosa Liboschitz var. purpurae, Lycium chinense, Aquillaria agallocha, Poria cocos, Panax ginseng, and honey, has been widely used in traditional Oriental medicine as a vitalizing medicine or as the prescription for patients with age-associated disorders such as amnesia and stroke. However, the potential protective value of KOK for the treatment of polycystic ovarian syndrome (PCOS) is largely unknown. We investigated whether pre-ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
47
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 50 publications
3
47
0
Order By: Relevance
“…In this study, we investigated IR in PCOS model rats by measuring fasting blood insulin and glucose and calculating the HOMA-IR index. In line with previous reports [16], our data demonstrated stimulated IR in DHEA-treated ovaries which was then readily alleviated by oral administration of HLF.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we investigated IR in PCOS model rats by measuring fasting blood insulin and glucose and calculating the HOMA-IR index. In line with previous reports [16], our data demonstrated stimulated IR in DHEA-treated ovaries which was then readily alleviated by oral administration of HLF.…”
Section: Discussionsupporting
confidence: 93%
“…The method for establishment of PCOS rat model referred to the protocol described by Jang et al [16]. The experimental schema is illustrated in Figure 1.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ovary weight in postnatal DHEA‐treated rats was increased relative to that in controls; this was accompanied by ovarian cyst expansion, an increased number of cystic follicles, granular cell layer thinning, and thickening of the theca cell layer . DHEA‐treated mice showed normal ovary weight and growing follicle and CL populations …”
Section: Androgen‐induced Pcos Modelsmentioning
confidence: 97%
“…These results indicated that adlay extracts also contain components that could inhibit signal transduction pathways of the androgen receptor. Jang et al (2014) demonstrated that the traditional Chinese herb Kyung-Ok-Ko (KOK; qiong-yu-gao in Chinese; kei-gyokukou in Japanese) is a traditional Oriental medicine that can improve DHEA-induced PCOS in animal models. This study also used an animal model of DHEA-induced PCOS to demonstrate that the AHE-EA possessed significant inhibitory effects on hyperandrogenemia in PCOS rats; the AHE-EA improved IR, oxidative stress, liver function, and inflammatory responses in PCOS rats.…”
Section: Discussionmentioning
confidence: 99%